Ragam Bahasa dan Konstruksi Identitas Hibrida pada Konten TikTok @arab_ngapak: Kajian Sosiolinguistik - Riska Syawalia; Prembayun Miji Lestari; Eka Yuli Astuti (Faculty of Languages and Arts, Universitas Negeri Padang, 2026)
The development of social media platforms, especially TikTok, has given rise to new linguistic phenomena that are interesting to study sociolinguistically. This study aims to describe the variety of languages and linguistic characteristics in the content of @arab_ngapak TikTok accounts. Using a qualitative descriptive method with a sociolinguistic approach, data was collected from 12 videos uploaded in March–December 2025 through the free participation listening technique (SBLC) and the recording technique. Data analysis used the Miles and Huberman models. The main theoretical frameworks include Martin Joos' theory of linguistic diversity and the theory of Chaer and Agustina's language variation. The results showed three dominant language types: consultative, intimate, and casual, with the business variety being the most frequent due to the high level of promotional content. Prominent linguistic characteristics include the mixing of Arabic and Javanese codes of the Ngapak dialect as a form of hybrid identity enregistration, the use of pisuhan as a marker of group solidarity, and the simile language style. These findings contribute to understanding how content creators use a variety of languages to construct social identities in the digital space.